Identification and clinical relevance of PD-L1 expression in primary mucosal malignant melanoma of the head and neck. Issue 6 (December 2015) - Thierauf, Julia; Veit, Johannes A.; Affolter, Annette; Bergmann, Christoph; Grünow, Jennifer; Laban, Simon; Lennerz, Jochen K.; Grünmüller, Lisa; Mauch, Cornelia; Plinkert, Peter K.; Hess, Jochen; Hoffmann, Thomas K.
Abstract : Mucosal melanoma of the head and neck is a rare and aggressive tumor entity with a poor prognosis. The standard treatment is radical tumor resection, with or without adjuvant radiation, where conventional chemotherapies in advanced stage or recurrent diseases have shown little benefit. Overexpression of the programmed cell death ligand 1 (PD-L1) is a common feature in human cancer. Although PD-L1 is an acknowledged prognostic biomarker for dismal prognosis in other tumors of the head and neck, expression and clinical relevance of PD-L1 in mucosal melanoma have not been addressed so far. We assessed PD-L1 expression using immunohistochemical staining in 23 tumor samples from patients with primary mucosal melanoma and correlated expression status with clinicopathological and outcome data. Tumors were derived from the nasal cavity (43.5%), nasal sinuses (43.5%), and the conjunctiva (13%). All patients had undergone surgery; 39% of all patients received adjuvant radiation and 13% were administered systemic interferon therapy. The probability of 1- and 5-year overall survival was 87 and 34.8%, respectively. The mean overall survival was 51 months and the mean recurrence-free survival was 23 months. Immunohistochemical staining showed PD-L1 expression in 13% (3/23) of mucosal melanoma. In contrast, prominent PD-L1 staining was detected in 100% of tissue sections from a control group of cutaneous melanoma ( n =9). PD-L1 expression in mucosal melanoma was not correlated with age, sex, nor anatomical localization of the tumor. Interestingly, patients with PD-L1-positive mucosal melanoma had a significantly longer recurrence-free survival ( P =0.026). In contrast to cutaneous melanoma and some other malignancies, a relevant PD-L1 overexpression in mucosal melanoma could not be confirmed.